A study of the genus Agrilaxia Kerremans, 1903 from French Guiana (Coleoptera: Buprestidae: Anthaxiini) - Bílý, Svatopluk (Zootaxa, 2017)
Description of four new species of the genus Agrilaxia Kerremans, 1903 from French Guiana: Agrilaxia (Agrilaxia) angustiptera sp. nov., A. (A.) antennata sp. nov., A. (A.) nigra sp. nov. and A. (A.) nigropurpurea sp. nov. New distributional data are given for Agrilaxia (A.) chrysifrons (Kerremans, 1896) and the previously unknown male genitalia of this species is illustrated.